Cavernous haemangioma of the thyroid mimicking benign nodule- a diagnostic dilemma - Kumar, Balkrishna; Thangavel, Saranya; Raja, Kalaiarasi; Ganesh, Rajesh Nachiappa; Saxena, Sunil Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Cavernous haemangioma of the thyroid usually presents as a benign, solitary nodule mimicking colloid goitre. Depending upon the size, the symptoms may vary. Here we present a similar case report of a patient for whom we couldn’t make a definite diagnosis clinically or radiologically or by cytology. The patient underwent surgery and biopsy was reported as cavernous haemangioma of thyroid. Post-operative period was uneventful.